THE EFFECT OF PERCEPTION ON OBESITY AND ALCOHOL DRINKING PREDIABETES CAUSES TYPE 2 DIABETES MELLITUS IN TORAJA ETHNIC IN SOUTH SULAWESI PROVINCE - Oruh, Shermina; Nurgadima Achmad Djalaluddin; Lukman Waris (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
The prevalence of Diabetes Mellitus (DM) has been increasing in the world for several decades. The International Diabetes Federation predicts the global prevalence of DM to be 382 million in 2013 and 529 million in 2035 and will continue to increase until 22 next year. Indonesia ranks fourth after India, China, and America. Before becoming T2DM, most sufferers experienced prediabetes. Prediabetes to T2DM is influenced by socio-cultural factors including perceptions about obesity and consuming alcohol. This study aims to determine the effect of perceptions of obesity and prediabetes alcohol drinking as a cause of T2DM in the Toraja ethnic in South Sulawesi Province. Qualitative research design with the Rapid Assessment Procedure method. The population is prediabetic from biomedical samples in Tana Toraja and North Toraja Regencies, South Sulawesi Province Riskesdas 2013. The samples are residents with prediabetes and T2DM of the Toraja ethnic group who live in Tana Toraja and North Toraja regency. Information gathering was carried out in 2018 through focus group discussions on two groups (prediabetes and T2DM). In-depth interviews with health service program managers, health center staff, health cadres, and community leaders. Research explains that there is an influence on perceptions of obesity and alcohol drinking in pre-diabetic Toraja people who cause T2DM. Obesity is perceived as a sign that a person has prospered in life, while an alcoholic drink called tuak is the drink consumed daily by the Toraja people.